2005
DOI: 10.1007/s10493-005-1117-x
|View full text |Cite
|
Sign up to set email alerts
|

Semiochemicals Influencing the Host-finding Behaviour of Varroa Destructor

Abstract: Studies of Varroa destructor orientation to honey bees were undertaken to isolate discrete chemical compounds that elicit host-finding activity. Petri dish bioassays were used to study cues that evoked invasion behaviour into simulated brood cells and a Y-tube olfactometer was used to evaluate varroa orientation to olfactory volatiles. In Petri dish bioassays, mites were highly attracted to live L5 worker larvae and to live and freshly freeze-killed nurse bees. Olfactometer bioassays indicated olfactory orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
0
34
0
1
Order By: Relevance
“…This assay clearly showed that inhibition of EP responses to nurse honey bee volatiles correlates with a profound behavioral change: a total reversal of the commonly observed [15],[10]],[36] nurse preference by the mite. An expected behavioral effect of a chemosensory disruptive compound would be a lack of preference, yet in this case the inhibiting compounds caused an inversion in preference.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This assay clearly showed that inhibition of EP responses to nurse honey bee volatiles correlates with a profound behavioral change: a total reversal of the commonly observed [15],[10]],[36] nurse preference by the mite. An expected behavioral effect of a chemosensory disruptive compound would be a lack of preference, yet in this case the inhibiting compounds caused an inversion in preference.…”
Section: Discussionmentioning
confidence: 72%
“…In laboratory bioassays Varroa has been shown to discriminate between bees from different task groups and to prefer a nurse over a forager [10], [11]. The host preference is apparently based on both low volatility compounds, such as cuticular hydrocarbons [12], and on volatile compounds emitted by the honey bees and their environment (such as larval food and brood pheromone) [13][15]. Despite much progress in the identification of host olfactory cues guiding Varroa , neither effective attractants nor repellents have been found so far.…”
Section: Introductionmentioning
confidence: 99%
“…Greater levels on brood combs were probably due to mites preferring nurse bees, which tend to stay on brood combs (Pernal et al 2005). The differences may have been underestimated in our study, to the extent that bees may have been redistributed among frames when colonies were opened for sampling.…”
Section: Discussionmentioning
confidence: 68%
“…Honeybees are among the most well studied living organisms [102]. They accumulate a variety of resources attractive to various arthropods including the small hive beetles, Aethina tumida Murray, the African large hive beetle, Oplostomus haroldi Witte and O. fuligineus Olivier, and the invasive mite, Varroa destructor Anderson & Trueman [102,103,104,105,106,107,108,109,110]. These invaders exploit hive resources as food for adults and immatures, and as oviposition sites [105].…”
Section: Management Of the Greater Wax Mothmentioning
confidence: 99%